ANALISIS KELAYAKAN KOMPENSASI GURU APARATUR SIPIL NEGARA (ASN) SMA/SMK NEGERI DI INDONESIA MELALUI FRAMEWORK PAY DETERMINATION - Iffah Nanda Sukendra; Delvia Nayyara; Faizah Amaliyah Budiman; Tyas Wida Handoko (STKIP Pesisir Selatan, 2026)
As times change, the role of teachers has become crucial in shaping the direction of education, designing learning programmes, and educating students. To perform their duties, teachers need to possess high levels of motivation, job satisfaction and discipline. One key factor that can influence these three aspects is compensation. However, the compensation currently provided to teachers is neither adequate nor commensurate with their work. Therefore, this study aims to provide an overview of the influence of teacher compensation, particularly for civil servant teachers at Senior High School, on motivation, job satisfaction, and discipline, as well as to analyse the adequacy of teacher compensation using Berman’s (2016) Pay Determination framework. The research method is Systematic Literature Review (SLR) using Systematic Mapping Study (SMS) approach. The results of this study indicate that the influence of teachers’ compensation on motivation, job satisfaction, and discipline is predominantly positive and significant. Meanwhile, the results of the analysis of teachers’ compensation using the Pay Determination framework indicate that the current compensation for civil servant teachers at Senior High Schools does not yet meet the compensation determination standards according to the Pay Determination framework, in terms of philosophy, the labour market, job evaluation, and individual considerations